Molecular markers and their application in Fusarium wilt studies in Musa spp. - Arinaitwe, Ivan Kabiita; Chee, How Teo; Fatimah Kayat,; Tumuhimbise, Robooni; Uwimana, Brigitte; Kubiriba, Jerome; Jennifer Ann Harikrishna,; Rofina Yasmin Othman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Bananas and plantains (Musa spp.) are an important socio-economic fruit crop grown worldwide. Their production across the regions where they are grown is largely hampered by pests and diseases. Fusarium wilt is a disastrous diseases of bananas caused by the fungal pathogen Fusarium oxysporum f.sp. cubense (Foc). Managing it with chemicals, biological control agents and cultural methods is ineffective. Host plant resistance is the most effective and durable approach of managing most pest and disease epidemics in most plant species and could equally be effective in managing Fusarium wilt in bananas. Crossbreeding as one of the ways to introgress disease resistance genes and phenotyping for biotic and abiotic stresses currently used in banana breeding is apparently difficult to apply because of banana’s low fertility, gigantic size, and long-life cycle which prolongs its breeding cycle. There is, therefore, a need to apply molecular markers in banana genetic improvement for Fusarium wilt resistance because of their accuracy, speed, robustness and effectiveness of operation. The objective of this article was to review and discuss molecular markers that have been successfully used in studying Fusarium wilt in bananas and some other important crops. Molecular markers discussed in this article include Random Amplified Polymorphic DNA, Sequence Characterized Amplified Region, Simple Sequence Repeat, Inter-Simple Sequence Repeat, and Single Nucleotide Polymorphism. The information discussed in this article informs future decisions to identify suitable marker systems for fine mapping of target regions and accelerated identification of quantitative trait loci for Foc resistance in bananas.